Exploring the branding and marketing communications strategies of Nottingham MBA in China - Jiang, Baitao (2011)
Background The MBA education becomes more popular nowadays. The competition amongst MBA programmes in different countries is being increasingly fierce. In order to diversifies the source of students and expend the market, MBA programmes pursue to entry overseas markets. As a result, the competition of the MBA market is changing from nationally to internationally. MBA programme managers start to apply marketing knowledge to competing for the students globally. As a high level and expensive, branding is deemed to be the key factor influencing student’s decision. In addition, marketing communications mix is treated as a major tool to support the brand equity. Therefore, the role of brand equity and marketing communication is being more important for MBA programmes. Nottingham University as an old UK university with reputation worldwide attracts a vast number of applicants every year, in particular Chinese students. However, in the past few years, the MBA recruitment of the university in China declined significantly. According to preliminary observation and the review of the interim report provide by the MBA office, it is estimated that the issues are related to the ineffective branding and marketing communications strategy. Therefore, based on the relevant theories, this study aims at researching the branding and marketing communications issues of the Nottingham MBA in the China market, in order to improve the performance of the recruitment of the university.